THE IMPLEMENTATION OF DUOLINGO TO TEACH DESCRIPTIVE TEXT IN SCIENTIFIC APPROACH - Dyah Ayu; Anita Anggraeni (PROJECT (Professional Journal of English Education), 2020)
Reading is a process of communication. The process of reading can be stated through direct communication or by writing as well imagination of the reader that can be expressed in daily activities. This article discussed how to apply the Duolingo application using techniques that apply a scientific approach method in teaching reading process. The subject of this research consist of 38 students. The aim of this article was to find out the extent of the students understanding in reading seeing the right words and readings that are in the application. Descriptive qualitative was used in this research. Based on the result, Duolingo application that applied in learning descriptive text can help the students in learning process. Keywords:  Duolingo, Reading, Descriptive Text, Scientific Approach